2014
DOI: 10.1002/ejsp.2073
|View full text |Cite
|
Sign up to set email alerts
|

Nostalgia counteracts self‐discontinuity and restores self‐continuity

Abstract: Nostalgia is a resource that functions, in part, as a response to self-discontinuity and a source of self-continuity. We tested and supported this regulatory role of nostalgia in the tradition of establishing a causal chain. In Study 1, we examined the naturalistic association between events precipitating self-discontinuity and nostalgia. Self-discontinuity, especially when stemming from negative life events, was associated with higher proneness to nostalgia. In Study 2, we experimentally induced negative self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
264
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(291 citation statements)
references
References 75 publications
25
264
0
2
Order By: Relevance
“…We expected that individuals who were more Yugonostalgic would also more readily seek contacts with ethnic out-group members from former Yugoslavia, because through such contacts they could psychologically restore the past that they longed for. This is in line with research showing that nostalgia functions as a coping mechanism to deal with identity discontinuity (Sedikides, Wildschut, Routledge, & Arndt, 2015), and with research that indicates that nostalgia about an encounter with an out-group member is associated with a Collective Memory of a Dissolved Country 592 sense of having a shared identity and more positive out-group attitudes (Turner, Wildschut, & Sedikides, 2012).…”
Section: Yugonostalgiasupporting
confidence: 88%
“…We expected that individuals who were more Yugonostalgic would also more readily seek contacts with ethnic out-group members from former Yugoslavia, because through such contacts they could psychologically restore the past that they longed for. This is in line with research showing that nostalgia functions as a coping mechanism to deal with identity discontinuity (Sedikides, Wildschut, Routledge, & Arndt, 2015), and with research that indicates that nostalgia about an encounter with an out-group member is associated with a Collective Memory of a Dissolved Country 592 sense of having a shared identity and more positive out-group attitudes (Turner, Wildschut, & Sedikides, 2012).…”
Section: Yugonostalgiasupporting
confidence: 88%
“…The theory states that people strive to construct and maintain a sense of self-continuity, and that succeeding in this task may have important implications for personal and societal well-being. Studies have shown evidence that individuals strive to achieve and maintain a sense of self-continuity (Sedikides, Wildschut, Routledge, & Arndt, 2015;Shrauger, 1975; Troll & Skaff, 1997;Vignoles, Regalia, Manzi, Golledge, & Scabini, 2006; SELF-CONTINUITY ACROSS CULTURES 8 Vignoles, Manzi, Regalia, Jemmolo, & Scabini, 2008), and that deficits or threats to selfcontinuity are associated with negative personal and societal outcomes, including low selfesteem, dissociation, negative intergroup attitudes, and suicidality (Ball & Chandler, 1989;Lampinen, Odegard, & Leding, 2004; Rosenberg, 1986;Smeekes & Verkuyten, 2015).People may construct a sense of self-continuity in different ways. Focusing on pastto-present continuity, Chandler and colleagues (2003) proposed and found that "continuity warrants"-the reasons that people gave when asked explicitly to justify their selfcontinuity-could be classified into two different 'streams', which they called 'essentialist'…”
mentioning
confidence: 99%
“…However, people may also bolster their sense of self-continuity on a more implicit and intuitive level, without engaging in explicit reasoning. Sedikides et al (2015) showed that feelings of nostalgia for one's past can increase self-continuity, and that people may compensate for discontinuities by using nostalgia to restore self-continuity. Research has also suggested that people use cherished possessions to bolster self-continuity, especially during major life-transitions (Habermas & Paha, 2002;Kroger & Adair, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a totemic text becomes profoundly enmeshed as a resource of meaning-making, of self-identity, self-narrative and self-continuity. Symbolic threats may emerge that threaten the sanctity of the totemic relationship between self and object, and can induce nostalgic narratives as a method of meaning preservation as a regulatory and restorative balm (Sedikides et al, 2015). These threats may take multiple forms, as we have seen, including the strategy of rebooting, whereby a new text "writes over" an extant narrative totem to begin again in a distinct spatiotemporal location.…”
Section: Ghostbusters In (Development) Hellmentioning
confidence: 99%